Parenting and child temperament. The role of father involvement - Amaral, R.; Monteiro, L.; Santos, C.; Neves, A. (26th ISSBD Biennial Meeting of the International Society for the Study of Behavioural Development (Conference canceled), 2020)
In recent years, social changes and new family polices have led to an increase participation of fathers in childcare and family life (Wall et al., 2016). Considering that the father’s role is less culturally defined and more susceptible to the influence of individual and contextual determinants, it’s relevant to analyze variables facilitating or inhibiting parenting, in father’s perspectives (Belsky, 1984). Father’s individual, child characteristics and contextual factors should be considered. Recent research shows that child temperament affects the parenting practices adopted by fathers (Boost et al., 2010). Also, father’s involvement in children’s life, seems to contribute to the quality of parenting (Monteiro et al., 2017). The present study aims to analyze predictors of positive and negative parenting, considering father’s (age and education), and child’s characteristics (age, sex, temperament), as well as father’s participation in child related activities and his working status. The moderating role of father involvement in the relations between child’s temperament and parenting is tested. Method: 225 nuclear families (mother, father and focal child). All children (preschoolers) attended day-care centers. Fathers completed the Parenting Styles and Dimensions Questionnaire (Robinson et al., 2001) and mothers completed the short version of Children’s Behavior Questionnaire (Putnam & Rothbart, 2006). Both parents completed, independently, the Parental Involvement Scale (Monteiro et al., 2008). Results: Multiple hierarchical regression models were conducted, including five blocks of predictors (child sociodemographic, child temperament, father’s sociodemographic, father’s involvement, and interaction effects between involvement and child temperament). For Positive Parenting (F(13,212)=2.046; p = .02 R2a= .06), Negative Affect (b= -1.597, p=.03) was a significant predictor. An interaction effect was also found between Negative Affect and Teaching/Discipline (b= 2.149, p=.02). For Negative Parenting (F(13,212)=3.882; p=.00, R2a= .14) only fathers education was a significant predictor (b= -.164, p =.02). The results are discussed regarding the impact of child characteristics in parenting.